PENERAPAN PIJAT COMPRESSION MENGGUNAKAN ALAT PIJAT KAYU TERHADAP NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI PUSKESMAS SELATBARU KABUPATEN BENGKALIS - Yeni, Heni Heri; Wiji, Rizki Natia (Ensiklopedia of Journal, 2025)
During pregnancy, a mother experiences changes that occur both physically and psychologically and the changes that occur during pregnancy often become complaints for pregnant women, including swelling of the legs and feet and back pain. Treatment of back pain with compression massage therapy using wooden massage tools with the result that compression massage therapy is effective in treating back pain. The aim of this research was to determine the effect of applying compression massage using a wooden massage tool on back pain in third trimester pregnant women at the Selatbaru Community Health Center, Bengkalis Regency. The type of experiment used in this research is pre experiment with the research design used is one group pre test post test design. The population in this study was all pregnant women in the third trimester in September 2024, totaling 30 people, the sample size was 23 respondents and the sampling technique used a purposive sampling technique. This research instrument used SOP, while for measuring back pain this researcher used the Faced Pain Scale-Revise. The results of analysis using the paired t-test statistical test showed that the p-value = 0.000 < α = 0.05. Compression massage using a wooden massage tool for back pain is very influential because of its role as a pain relief system.  The output of this research is to make wooden massage products/tools. The conclusion is that there is an effect of applying compression massage using a wooden massage tool on back pain in third trimester pregnant women. Suggestions for third trimester pregnant women who experience back pain to increase knowledge about back massage and how to massage the back. This can be implemented by involving your husband (family) to do a back massage at home. Keywords: Back Pain, Compression Massage, Third Trimester Pregnant Women